"Periodic fever" without fever: two cases of non-febrile TRAPS with mutations in the TNFRSF1A gene presenting with episodes of inflammation or monosymptomatic amyloidosis. Issue 7 (24th November 2005) - Kallinich, T; Haffner, D; Rudolph, B; Schindler, R; Canaan-Kühl, S; Keitzer, R; Burmester, G R; Roesen-Wolff, A; Roesler, J
Abstract : Background: Tumour necrosis factor (TNF) receptor associated periodic syndrome (TRAPS) is caused by dominant mutations in the TNFRSF1A gene. In typical cases TRAPS begins early in childhood and is characterised by high and remittent fever over a period of 1–4 weeks or longer, accompanied by systemic and local inflammation. Case reports: Patient 1 presented with recurrent episodes of weakness, migrating myalgias, arthralgias, exanthema, and chest pain lasting for 1–4 weeks, but without any fever over an initial period of 4 years at least. Diagnosis of TRAPS was confirmed by the heterozygous mutation Y20H in TNFRSF1A . Patient 2, a 23 year old woman never had any symptoms indicative of TRAPS. Genetic evaluation of all members of her family with a TRAPS index patient disclosed the T50M mutation in TNFRSF1A . A medical check up showed proteinuria, and renal biopsy disclosed AA amyloidosis. Conclusions: TRAPS associated mutations can induce considerable inflammation that is not necessarily accompanied by fever. Even monosymptomatic severe amyloidosis can occur in these patients. Genetic counselling and appropriate management to prevent or mitigate amyloidosis may be necessary.